STUDI PEMIKIRAN MUHAMMAD ABDUH DAN PENGARUHNYA TERHADAP PENDIDIKAN DI INDONESIA - Komaruzaman Komaruzaman (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2017)
The purpose of writing this article is to find out how the life and education history, the concept of educational renewal, and how the influence of education renewal of M. Abduh in Indonesia. M. Abduh is a reformer figure in the 19th century whose ideas are very brilliant for Islamic renewal. He can revive the fighting spirit of Muslims to continue to advance in the field of science after experiencing phase kejumudan. The idea of ​​renewal of Abduh was a very big influence on education at that time and still alienated until now. He initiated an educational curriculum based on science and philosophy that uses reason by not abandoning religious lessons. Its influence came to Indonesia. Keywords: M Abduh Thought, Education in Indonesia